PREDOMINANCE, ELEMENTS AND BRAIN RESEARCH OF SPOUSAL SAVAGERY IN BANGLADESH: A SIMILAR REPORT ON COUNTRY METROPOLITAN ATTRIBUTES - Abdur Razzak (International Scientific and Current Research Conferences, 2021)
A few examinations have demonstrated that aggressive behavior at home against ladies, particularly savagery executed by a ladies' significant other is a difficult issue in Bangladesh. Accessible data from research showed that the most well-known kind of savagery against ladies in Bangladesh is aggressive behavior at home executed by cozy accomplices or ex-accomplices. In Bangladesh, the vast majority of the ladies experience aggressive behavior at home because of a cozy accomplice or relative in the course of her life.